Sudden Death Syndrome and Soybean Planting Date - Eric Adee; C. R. Little; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2017)
The effect of planting date on severity of sudden death syndrome (SDS) and yield was evaluated for the second year in two studies at the Kansas River Valley experiment fields in 2016. One study was established to promote SDS and the other to minimize SDS. In both studies the severity of SDS was greatest with the earlier planting dates. The yield was greatest with the earlier planting date, except for the most susceptible variety. The severity of SDS was not as great as had been observed in previous years. There is a very positive benefit to planting in early May when measures are taken to reduce the severity of SDS, such as variety selection.
Keywords: sudden death syndrome; SDS; phosphorus; soybeans; fertility